“O’er-dyed blacks” (1.2.131) : les couleurs dans Le Conte d’hiver - Sophie Chiari (Sillages Critiques)
In this paper, I intend an in-depth examination of the highly symbolical universe of colours in Shakespeare’s The Winter’s Tale against the background of the Reformation, which gave pride of place to dark and sad dyes. In the wake of Michel Pastoureau’s works on the subject, I will thus not only aim at exploring the broad chromatic fields of the play (black, white and red) but also at having a closer look at its “sentimental” colours (yellow and green) as well as at its “dishonest” hues (the colours of the rainbow), as those defended by Autolycus, whose polychrome world reflects a subversive vision of Bohemia. This analysis will lead us to question the playwright’s aesthetic values at work in the last scene of the play, which stages the beautifully painted—albeit wrinkled—statue of Hermione.